The effect of the (K.W.L.H) strategy in learning the skill of smashing in volleyball for second-stage female students, College of Physical Education and Sports Sciences - Fathel, Haider (Journal of Physical Education, 2025)
The importance of the study stands out in identifying the impact of the learning style for mastery in the educational process in general and skill learning in particular, through which learners can reach mastery in performing skills equally by giving the appropriate opportunity to all learners and providing sufficient time to learn the required skills, as well as Learners can be given additional time to enable them to acquire the required skills if the specified time is not sufficient The problem of the research lies in the dependence of some teachers in the process of learning the skills of the game of volleyball, including the skill of crushing hitting, educational methods and methods that do not achieve great benefit from the learning process, which made the educational process a process that moves away in most of its aspects from excitement and suspense. The study aimed to find out the impact of the learning style for the empowerment of those with motor performance difficulties for the students of the second academic year, and to know the effect of the learning style for the empowerment of those with motor performance difficulties in learning the skill of hitting the volleyball for the students of the second school year, and to know the effect preference of the learning style for mastery In learning the skill of crushing hitting the volleyball and the method used between the pre and post tests.The research assumed: that there are statistically significant differences between the results of the pre and posttests in learning the skill of crushing hitting the volleyball for people with motor performance difficulties for the experimental and control groups, there are statistically significant differences between the results of the tests of the experimental and control groups in learning the skill of crushing hitting the volleyball for students with difficulties Dimensional motor performance.   The researcher used the experimental method with the design of equal groups, random selection with pre and posttest, and the study was conducted on second year students in the College of Physical Education and Sports Sciences / University of Diyala for the academic year 2021/2022, whose number is (40) students, who were divided into two groups, control and experimental. With (20) students per group, the experimental group implemented the method of learning in order to empower those with motor performance difficulties, and the control group implemented the method used in the college, as the experiment included educational units implemented for the period from 3/20/2022 to 4/25/2022 by (8) educational units for the skill of overwhelming multiplication, and the time of one educational unit was (90) minutes.One of the most important conclusions reached by the researcher is that the use of a scale for people with motor performance difficulties for the skill of crushing hitting with volleyball has achieved a positive effect in identifying students who have difficulties in motor performance in the research task.The research recommends the need to introduce the curriculum prepared with the learning method for mastery, which is based on giving additional time invested in providing corrective feedback and explanatory information for basic skills in volleyball to benefit from it in the educational process